2023
DOI: 10.3390/coatings13101682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anthocyanins on Colorimetric Indicator Film Properties

Lin Chen,
Wenli Wang,
Wei Wang
et al.

Abstract: Nowadays, intelligent packaging has become very popular. It can quickly detect problems that arise during food production or circulation by monitoring the quality and safety of food. Anthocyanins have attracted widespread attention as a material for manufacturing smart food packaging, as they are sensitive to changes in pH, and small changes in pH can cause changes in the color of anthocyanins. The incorporation of anthocyanins often causes different changes in the properties of the films. The effects of antho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Having this in mind, several studies have been reported in the literature to assess the degree of conservation of perishable foods such as meat, fish, and dairy products using pH-sensitive natural dyes, namely anthocyanins, to develop colorimetric pH-responsive films that act as indicators of food freshness in real-time. However, the use of such dyes for these applications is still limited because they lose more than 50% of their color between pH 4 and 7, a critical range for monitoring color changes during food spoilage, due to the establishment of a complex chemical equilibrium network involving reversible reactions such as hydration, tautomerization, isomerization, as well as irreversible oxidative degradation mechanisms. …”
Section: Introductionmentioning
confidence: 99%
“…Having this in mind, several studies have been reported in the literature to assess the degree of conservation of perishable foods such as meat, fish, and dairy products using pH-sensitive natural dyes, namely anthocyanins, to develop colorimetric pH-responsive films that act as indicators of food freshness in real-time. However, the use of such dyes for these applications is still limited because they lose more than 50% of their color between pH 4 and 7, a critical range for monitoring color changes during food spoilage, due to the establishment of a complex chemical equilibrium network involving reversible reactions such as hydration, tautomerization, isomerization, as well as irreversible oxidative degradation mechanisms. …”
Section: Introductionmentioning
confidence: 99%